Sole and preparation method thereof
By stacking the anti-slip layer composed of inorganic compound particles on the sole sole, the problem that the existing rubber sole does not have anti-slip function on the ice surface is solved, and the high friction coefficient of the sole on the ice surface is achieved, reducing the risk of slipping Effect.
Patent Information
- Application Number
- CN202411768220.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
The existing rubber soles do not have the function of preventing ice on the ice surface, which makes it easy to slip and fall when walking on slippery and icy roads.
Design a sole, including a sole embryo and a non-slip layer stacked on the sole embryo. The anti-slip layer consists of inorganic compound particles and a surface treatment agent for bonding, and the edges and ends of some inorganic compound particles are exposed on the sole surface.
By exposed the edges and ends of the inorganic compound particles, the friction coefficient of the sole on the ice is significantly increased, effectively reducing the risk of slipping and protecting outdoor athletes from physical harm caused by slipping.
Smart Images

Figure CN119431909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soles, and in particular to a sole and a preparation method thereof. Background Art
[0002] For rubber used in shoes, good anti-skid property is one of the basic functions that rubber products for soles should have, and it is also an important indicator to measure the quality of shoes. The anti-skid property of the sole refers to the anti-skid effect or grip of the sole on the ground. The quality of the anti-skid property is directly related to the safety of the shoes when worn. If the anti-skid property of the sole is not good, it is easy to slip and fall when walking on wet and icy roads. In most parts of northern my country, the temperature is low in winter, and the road surface is prone to water accumulation and ice, making it easier for people to slip when walking on it.
[0003] Common rubber soles currently available on the market do not have the function of preventing slipping on ice. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to a certain extent. To this end, the present invention provides a sole and a preparation method thereof.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a sole, 1. A sole, characterized in that it comprises a sole embryo and an anti-slip layer stacked on the bottom surface of the sole embryo;
[0006] The sole blank comprises the following raw materials in parts by weight: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent;
[0007] The anti-skid layer includes an anti-skid matrix and a plurality of inorganic anti-skid particles dispersed in the anti-skid matrix, and a portion of the inorganic anti-skid particles are exposed from the surface of the anti-skid matrix.
[0008] The present invention has the following beneficial effects: the anti-skid particle layer contains inorganic compound particles, and the corners of some inorganic compound particles are exposed on the sole surface. During the friction between the sole and the ice surface, the inorganic compound particles will participate in affecting the friction performance of the sole. The corners of these inorganic compound particles provide the sole with grip on the ice surface, so that the friction coefficient of the ice surface is significantly increased regardless of whether it is in a dry state or a water-lubricated state. The risk of slipping is effectively reduced, and the body injury caused by slipping in outdoor sports is better protected.
[0009] Preferably, the anti-slip matrix is made of a bonding surface treatment agent, and in the anti-slip layer, the mass ratio of the inorganic anti-slip particles to the bonding surface treatment agent is 1:(0.02-0.03).
[0010] Preferably, the plurality of inorganic compound particles include:
[0011] Silicon carbide particles: 30-50 parts;
[0012] Boron carbide particles: 50-70 parts.
[0013] Preferably, the average particle size of the silicon carbide particles is 1-3 mm, and the average particle size of the boron carbide particles is 2-4 mm.
[0014] Preferably, the rubber antioxidant is selected from any one of antioxidant 4010, antioxidant 4010NA and antioxidant 4020.
[0015] The second aspect of the present invention provides a method for preparing the sole provided by the first aspect of the present invention, comprising the following steps:
[0016] The shoe sole blank is prepared by using the following raw materials in parts by mass: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent;
[0017] Dispersing a plurality of inorganic anti-skid particles in an anti-skid matrix to form an anti-skid layer;
[0018] The anti-slip layer and the sole blank are stacked in sequence and hot-pressed and molded to obtain the sole.
[0019] Preferably, the sole blank is made of the following raw materials in parts by mass: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent; specifically including:
[0020] Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 70-80 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 120-130 degrees, discharge the rubber to obtain a rubber compound.
[0021] The rubber material is put into an open mixer and thinned 2-4 times, with the thickness of each thinning being 0.5-0.8 mm, to obtain a semi-finished film;
[0022] The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.3-1.5 parts by weight relative to 100 parts by weight of the semi-finished film, and the film is opened for 10-12 minutes to obtain a finished film;
[0023] The finished film is cut into a sole shape to obtain a sole blank.
[0024] Preferably, the step of dispersing a plurality of inorganic anti-skid particles in an anti-skid matrix to form an anti-skid layer specifically comprises:
[0025] After the silicon carbide particles and the boron carbide particles are mixed, a bonding surface treatment agent is added, and the mixture is stirred until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and the anti-slip layer is obtained after drying.
[0026] Preferably, the anti-slip layer and the sole blank are stacked in sequence and hot-pressed to obtain the sole; specifically comprising:
[0027] Heat the sole mold to 155-165 degrees, open the sole mold, place 10-15g of the anti-slip layer at the sole and heel, then put the sole blank in to cover the anti-slip layer;
[0028] The shoe sole mold is closed and heated for 300-600 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out;
[0029] The semi-finished sole product is polished so that 1-2 mm of the silicon carbide particles and the boron carbide particles are exposed on the bottom surface of the semi-finished sole product to obtain a sole.
[0030] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and drawings. The best embodiments or means of the present invention will be described in detail in conjunction with the drawings, but they are not intended to limit the technical solutions of the present invention. In addition, there are multiple features, elements, and components that appear in each of the following texts and drawings, and different symbols or numbers are marked for convenience, but they all represent components with the same or similar structures or functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings:
[0032] Figure 1 It is a schematic diagram of the sole structure of the present invention.
[0033] Figure 2 It is a flowchart of the preparation method of the present invention.
[0034] Explanation of the accompanying drawings: 1. sole embryo; 2. anti-skid particle layer. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments in the implementation manner are intended to be used to explain the present invention and should not be construed as limiting the present invention.
[0036] References in this specification to "one embodiment" or "an example" or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment itself may be included in at least one embodiment of the present patent disclosure. The appearance of the phrase "in one embodiment" in various places in the specification does not necessarily refer to the same embodiment.
[0037] The first aspect of the present invention provides a sole, comprising a sole blank 1 and an anti-skid layer 2 stacked on the bottom surface of the sole blank 1; the sole blank 1 is composed of the following raw materials in parts by weight: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent;
[0038] The anti-slip layer 2 includes an anti-slip matrix and a plurality of inorganic anti-slip particles dispersed in the anti-slip matrix, and a portion of the inorganic anti-slip particles are exposed from the surface of the anti-slip matrix.
[0039] The anti-skid particle layer of the shoe sole provided by the present invention contains inorganic compound particles, and the corners of some inorganic compound particles are exposed on the surface of the shoe sole. During the friction between the shoe sole and the ice surface, the inorganic compound particles will participate in affecting the friction performance of the shoe sole. The corners of these inorganic compound particles provide the shoe sole with grip on the ice surface, so that the friction coefficient of the ice surface is significantly increased regardless of whether it is in a dry state or a water-lubricated state. The risk of slipping is effectively reduced, and the body injury caused by slipping in outdoor sports is better protected.
[0040] The anti-skid particle layer of this embodiment is made of inorganic compound particles and bonding surface treatment agent in a weight ratio of 1: (0.02-0.03). The inorganic compound particles are composed of the following raw materials in weight: 30-50 parts of silicon carbide particles and 50-70 parts of boron carbide particles. The average particle size of the silicon carbide particles is 1-3mm, and the average particle size of the boron carbide particles is 2-4mm. The properties of silicon carbide are between diamond and silicon, and it has the characteristics of high hardness, high heat resistance and excellent chemical corrosion resistance.
[0041] The white carbon black in this embodiment is fumed white carbon black. The antioxidant is selected from any one of antioxidant 4010, antioxidant 4010NA and antioxidant 4020.
[0042] The second aspect of the present invention provides a method for preparing the sole provided by the first aspect of the present invention, referring to Figure 2 , including the following steps:
[0043] S1. A sole blank is prepared by using the following raw materials in parts by mass: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent; the details are as follows:
[0044] Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 70-80 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 120-130 degrees, discharge the rubber to obtain a rubber compound.
[0045] The rubber material is put into an open mixer and thinned 2-4 times, with the thickness of each thinning being 0.5-0.8 mm, to obtain a semi-finished film;
[0046] The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.3-1.5 parts by weight, and the amount of the vulcanization accelerator is 1.5-1.8 parts by weight relative to 100 parts by weight of the semi-finished film, and the mixing is continued for 10-12 minutes to obtain a finished film;
[0047] The finished film is cut into a sole shape to obtain a sole blank.
[0048] S2, dispersing a plurality of inorganic anti-skid particles in an anti-skid matrix to form an anti-skid layer; specifically as follows:
[0049] After the silicon carbide particles and the boron carbide particles are mixed, a bonding surface treatment agent is added and stirred until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and an anti-slip layer is obtained after drying.
[0050] S3, stacking the anti-slip layer and the sole blank in sequence and hot pressing and molding them to obtain the sole. The details are as follows:
[0051] Heat the sole mold to 155-165 degrees, open the sole mold, place 10-15 grams of the anti-slip layer at the sole and heel, then put the sole blank in to cover the anti-slip layer;
[0052] The shoe sole mold is closed and heated for 300-600 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out;
[0053] The bottom surface of the semi-finished sole is polished with a wire wheel to expose the silicon carbide particles and the boron carbide particles on the bottom surface of the semi-finished sole, and the exposed parts of the silicon carbide particles and the boron carbide particles are 1-2 mm long to obtain a sole.
[0054] Example 1
[0055] Weigh 20 parts of natural rubber, 45 parts of butadiene rubber, 15 parts of styrene-butadiene rubber, 20 parts of brominated butyl rubber, 30 parts of white carbon black, 1 part of polyethylene glycol, 0.8 parts of stearic acid, 4 parts of zinc oxide, 0.5 parts of antioxidant, 0.7 parts of rubber antioxidant, 1 part of silane coupling agent; 30 parts of silicon carbide particles, 70 parts of boron carbide particles. The average particle size of the silicon carbide particles is 3 mm, and the average particle size of the boron carbide particles is 4 mm.
[0056] Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 70 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 120 degrees, discharge the rubber to obtain a rubber compound.
[0057] The rubber material is put into an open mixer and thinned for 3 times, each time the thickness of the thinning is 0.5 mm, to obtain a semi-finished film;
[0058] The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.3 parts by weight, and the amount of the vulcanization accelerator is 1.8 parts by weight relative to 100 parts by weight of the semi-finished film, and the mixing is continued for 10 minutes to obtain a finished film;
[0059] Cutting the finished film into a sole shape to obtain a sole blank;
[0060] After mixing the silicon carbide particles and the boron carbide particles, adding a bonding surface treatment agent and stirring until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and obtaining an anti-slip layer after drying for standby use;
[0061] Heat the sole mold to 155 degrees, open the sole mold, set 10 grams of the anti-slip layer at the position of the sole and the heel, and then put the sole blank into it to cover the anti-slip layer;
[0062] The shoe sole mold is closed and heated for 300 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out;
[0063] The bottom surface of the semi-finished sole is polished with a wire wheel to expose the silicon carbide particles and the boron carbide particles on the bottom surface of the semi-finished sole, and the exposed portion of the silicon carbide particles and the boron carbide particles is 1 mm long, thereby obtaining a sole.
[0064] Example 2
[0065] Weigh 20 parts of natural rubber, 60 parts of butadiene rubber, 27 parts of styrene-butadiene rubber, 30 parts of brominated butyl rubber, 40 parts of white carbon black, 1 part of polyethylene glycol, 0.5 parts of stearic acid, 3 parts of zinc oxide, 0.5 parts of antioxidant, 0.5 parts of rubber antioxidant, 1 part of silane coupling agent; 50 parts of silicon carbide particles, 60 parts of boron carbide particles. The average particle size of the silicon carbide particles is 1-3 mm, and the average particle size of the boron carbide particles is 2-4 mm.
[0066] Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 80 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 130 degrees, discharge the rubber to obtain a rubber compound.
[0067] The rubber material is put into an open mixer and thinned for 3 times, each time the thickness of the thinning is 0.8 mm, to obtain a semi-finished film;
[0068] The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.5 parts by weight, and the amount of the vulcanization accelerator is 1.5 parts by weight relative to 100 parts by weight of the semi-finished film, and the mixing is continued for 12 minutes to obtain a finished film;
[0069] Cutting the finished film into a sole shape to obtain a sole blank;
[0070] After mixing the silicon carbide particles and the boron carbide particles, adding a bonding surface treatment agent and stirring until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and obtaining an anti-slip layer after drying;
[0071] Heat the sole mold to 165 degrees, open the sole mold, place 15 grams of the anti-slip layer at the sole and heel, then put the sole blank in, covering the anti-slip layer;
[0072] The shoe sole mold is closed and heated for 600 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out;
[0073] The bottom surface of the semi-finished sole is polished with a wire wheel to expose the silicon carbide particles and the boron carbide particles on the bottom surface of the semi-finished sole, and the exposed portion of the silicon carbide particles and the boron carbide particles is 2 mm long, thereby obtaining a sole.
[0074] Example 3
[0075] Weigh 20 parts of natural rubber, 50 parts of butadiene rubber, 30 parts of styrene-butadiene rubber, 30 parts of brominated butyl rubber, 40 parts of white carbon black, 3 parts of polyethylene glycol, 0.5 parts of stearic acid, 3 parts of zinc oxide, 0.5 parts of antioxidant, 0.5 parts of rubber antioxidant, 2 parts of silane coupling agent; 30 parts of silicon carbide particles, 50 parts of boron carbide particles. The average particle size of the silicon carbide particles is 3 mm, and the average particle size of the boron carbide particles is 2 mm.
[0076] Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 80 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 125 degrees, discharge the rubber to obtain a rubber compound.
[0077] The rubber material is put into an open mixer and thinned 4 times, each time the thickness of the thinning is 0.8 mm, to obtain a semi-finished film;
[0078] The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.5 parts by weight, and the amount of the vulcanization accelerator is 1.7 parts by weight relative to 100 parts by weight of the semi-finished film, and the mixing is continued for 11 minutes to obtain a finished film;
[0079] Cutting the finished film into a sole shape to obtain a sole blank;
[0080] After mixing the silicon carbide particles and the boron carbide particles, adding a bonding surface treatment agent and stirring until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and obtaining an anti-slip layer after drying for standby use;
[0081] Heat the sole mold to 160 degrees, open the sole mold, place 15 grams of the anti-slip layer at the sole and heel, then put the sole blank in, and cover the mixture;
[0082] The shoe sole mold is closed and heated for 500 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out;
[0083] The bottom surface of the semi-finished sole is polished with a wire wheel to expose the silicon carbide particles and the boron carbide particles on the bottom surface of the semi-finished sole, and the exposed parts of the silicon carbide particles and the boron carbide particles are 1-2 mm long to obtain a sole.
[0084] Comparative Example 1
[0085] The difference from Example 3 is that no boron carbide particles are added.
[0086] Comparative Example 2
[0087] The difference from Example 3 is that no silicon carbide particles are added.
[0088] The sole density is measured according to GB / T533-2008, the sole volume wear is tested according to ASTM D5963-04 (2019), Method A, Load 10N method, and the anti-slip performance dynamic friction coefficient is measured according to GB / T3903.6-2017. The sole performance test results of each embodiment and comparative example are shown in Table 1:
[0089] Table 1
[0090]
[0091]
[0092] It is obvious from the above test results that Example 3 has excellent anti-slip performance. Inorganic particles are used to form protruding particles on the sole. It can be seen from the comparative example that the performance of the product is significantly reduced when boron carbide particles and boron carbide particles are not added. The performance effect of the product is the most excellent when the two are coordinated and synergistic.
[0093] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A shoe sole, characterized in that: It comprises a sole embryo and an anti-skid layer stacked on the bottom surface of the sole embryo; The sole blank comprises the following raw materials in parts by weight: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent; The anti-skid layer includes an anti-skid matrix and a plurality of inorganic anti-skid particles dispersed in the anti-skid matrix, and a portion of the inorganic anti-skid particles are exposed from the surface of the anti-skid matrix.
2. The sole according to claim 1, characterized in that The anti-skid matrix is made of a bonding surface treatment agent, and in the anti-skid layer, the mass ratio of the inorganic anti-skid particles to the bonding surface treatment agent is 1:(0.02-0.03).
3. The sole according to claim 2, characterized in that The plurality of inorganic anti-slip particles include: Silicon carbide particles: 30-50 parts; Boron carbide particles: 50-70 parts.
4. The sole according to claim 3, characterized in that The average particle size of the silicon carbide particles is 1-3 mm, and the average particle size of the boron carbide particles is 2-4 mm.
5. The shoe sole according to any one of claims 1 to 4, characterized in that: The rubber antioxidant is selected from any one of antioxidant 4010, antioxidant 4010NA and antioxidant 4020.
6. A method for preparing a sole according to any one of claims 1 to 5, comprising the following steps: The shoe sole blank is prepared by using the following raw materials in parts by mass: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent; Dispersing a plurality of inorganic anti-skid particles in an anti-skid matrix to form an anti-skid layer; The anti-slip layer and the sole blank are stacked in sequence and hot-pressed and molded to obtain the sole.
7. The preparation method according to claim 6, characterized in that: The sole blank is made of the following raw materials in parts by weight: 20-30 parts of natural rubber, 30-60 parts of butadiene rubber, 10-30 parts of styrene-butadiene rubber, 15-30 parts of brominated butyl rubber, 30-40 parts of white carbon black, 1-3 parts of polyethylene glycol, 0.5-0.8 parts of stearic acid, 3-4 parts of zinc oxide, 0.5-0.8 parts of antioxidant, 0.5-0.8 parts of rubber antioxidant, and 1-2 parts of silane coupling agent; specifically including: Put natural rubber, butadiene rubber, styrene-butadiene rubber and bromobutyl rubber into an internal mixer for internal mixing. When the temperature rises to 70-80 degrees, add white carbon black, polyethylene glycol, stearic acid, zinc oxide, antioxidant, rubber antioxidant and silane coupling agent. When the temperature rises to 120-130 degrees, discharge the rubber to obtain a rubber compound. The rubber material is put into an open mixer and thinned 2-4 times, with the thickness of each thinning being 0.5-0.8 mm, to obtain a semi-finished film; The semi-finished film is put into the open mill again, and a vulcanizing agent and a vulcanization accelerator are added, wherein the amount of the vulcanizing agent is 1.3-1.5 parts by weight, and the amount of the vulcanization accelerator is 1.5-1.8 parts by weight relative to 100 parts by weight of the semi-finished film, and the mixing is carried out for 10-12 minutes to obtain a finished film; The finished film is cut into a sole shape to obtain a sole blank.
8. The preparation method according to claim 6, characterized in that: The method of dispersing a plurality of inorganic anti-skid particles in an anti-skid matrix to form an anti-skid layer specifically comprises: After the silicon carbide particles and the boron carbide particles are mixed, a bonding surface treatment agent is added, and the mixture is stirred until the bonding surface treatment agent is evenly attached to the surfaces of the silicon carbide particles and the boron carbide particles, and the anti-slip layer is obtained after drying.
9. The preparation method according to claim 6, characterized in that: The anti-slip layer and the sole blank are stacked in sequence and hot-pressed and molded to obtain the sole; specifically comprising: Heat the sole mold to 155-165 degrees, open the sole mold, place 10-15g of the anti-slip layer at the sole and heel, then put the sole blank in to cover the anti-slip layer; The shoe sole mold is closed and heated for 300-600 seconds. After the molding is completed, the mold is opened and the semi-finished shoe sole is taken out; The semi-finished sole product is polished so that 1-2 mm of the silicon carbide particles and the boron carbide particles are exposed on the bottom surface of the semi-finished sole product to obtain a sole.